Producing mujtahid between tradition and contemporary - alkhatri, Maithah said abdillah; Haneef, Sayed Sikandar Shah; Alsaefi, Hosam eldin Ibrahin Mohamed (International Islamic University Malaysia, 2019)
Among the masterpieces of religious tradition of Prophet S.A.W. is the ability to cope with the events and developments and to absorb the diversity of temporal and spatial conditions, in line with the Islamic verses. Ijtihad is the duties of sufficiency that ones have to bear them. Therefore, whoever intends to close the door of Ijtihad has erred, since the issues of mankind changeable from day to day. Although there are small number of Ijtihad individually but there are Ijtihad collectively that played big role in finding solutions which arise among people. This study discussed the issues of producing Mujtahid, in terms of qualification and youthness, according to the stipulated conditions. The study found that it is important to have selection of qualified person to become mujtahid as well as the selected tests and interviews with high accuracy, so that they could overcome the obstacles and challenges later. The study also found that there should have a concern on the important learning system in producing mujtahid and the Islamic heritage as well.